2014
DOI: 10.3324/haematol.2013.101386
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MLL5 expression on decitabine efficacy and DNA methylation in acute myeloid leukemia

Abstract: Methods Patients with decitabine administrationThis study included 57 patients (aged >60 years) with de novo or secondary AML (following MDS or treatment-related AML) who were treated in trial 00331 (registration n. DRKS00000069) with 135 mg/m 2 total decitabine infused intravenously over 72 h every six weeks 16 or who received 20 mg/m 2 per day (Days 1-5) every four weeks. Patients were included in the present study if RNA was available and if the sample contained at least 30% blasts (median 55%). Fifty sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Indeed, the initial patterns of gene expression in patients treated with decitabine may influence the efficacy of this drug. For example, patients with low levels of lysine methyltransferase MLL5 were developing resistance to low‐doses of decitabine . In addition, expression levels of two enzymes involved in decitibine metabolism, namely cytidine deaminase and deoxycytidine kinase, differ between non‐responders and responders .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the initial patterns of gene expression in patients treated with decitabine may influence the efficacy of this drug. For example, patients with low levels of lysine methyltransferase MLL5 were developing resistance to low‐doses of decitabine . In addition, expression levels of two enzymes involved in decitibine metabolism, namely cytidine deaminase and deoxycytidine kinase, differ between non‐responders and responders .…”
Section: Discussionmentioning
confidence: 99%
“…Set3 complex (Set3C) was also recently tied to the DNA damage response operating under a model of altered histone acetylation dynamics ( Torres-Machorro et al 2015 ). MLL5 in mammals has been tied to several different cellular processes, including hematopoesis ( Heuser et al 2009 ; Madan et al 2009 ; Zhang et al 2009 ), cell cycle progression ( Deng et al 2004 ; Cheng et al 2008 ), oncogenesis ( Emerling et al 2002 ), and DNA methylation ( Yun et al 2014 ), though its exact mechanistic role or binding partners in these diverse functions have not been fully resolved. In Drosophila , upSET e00365/e00365 flies were described to be viable, but with a female fertility defect due to derepression of transposable elements in the ovary ( Rincon-Arano et al 2012 ).…”
mentioning
confidence: 99%
“…Previous studies have found that tumorigenesis and the metastasis of esophageal cancer result from the downregulation of the expression of multiple tumor suppressor genes and the abnormal hypermethylation of their promoters ( 33 35 ). Studies have shown that 5-azacytidine, a clinical chemotherapeutic drug used in the treatment of various types of cancer, inhibits the methylation of the promoter of multiple genes and affects the expression of these genes ( 39 , 40 ). In this study, we used EC9706 cells to assess the anticancer effects of 5-azacytidine in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%